Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fneur.2020.543485
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Migraine and Patent Foramen Ovale

Abstract: Background: Migraine is a widespread neurological disorder. The patent foramen ovale (PFO) is a remnant of the fetal circulation. Multiple studies suggest that migraine is more prevalent in subjects with PFO and vice versa. It is unclear if there is a causal relationship or simply a co-existence of these two conditions. Furthermore, the treatment of migraine with percutaneous closure PFO remains controversial.Methods: We reviewed studies pertaining to the relationship between PFO and migraine as well as the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 95 publications
0
35
0
3
Order By: Relevance
“…There is a dose-effect relationship between PFO and migraine. Larger PFO, permanent PFO, and anatomical variation of PFO can aggravate RLS, which is associated with migraine attacks [11]. Meanwhile, PFO is more associated with MA than MoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dose-effect relationship between PFO and migraine. Larger PFO, permanent PFO, and anatomical variation of PFO can aggravate RLS, which is associated with migraine attacks [11]. Meanwhile, PFO is more associated with MA than MoA.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that the incidence of patent foramen ovale (PFO) in migraine patients is signi cantly higher than that in normal people [9,10]. The relationship between PFO and migraine has been studied and is a major concern [11]. Vestibular migraine is considered to be related to vestibular symptoms caused by migraine mechanisms, and its pathogenesis may be related to ion channel defects, enhanced cortical excitability, and central sensitisation, which are caused by genetic susceptibility [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Schwerzmann et al have demonstrated that the number of people having small RLS among migraine patients and healthy subjects was similar but a moderate or large RLS occurred more frequently in the migraine group compared to healthy controls [22]. More remarkably, it has been argued that larger PFO, persistent PFO, and complex tissue structures may cause more RLS to increase the incidence of migraine [23]. These findings may reflect the "dose-response" relationship between RLS and migraine.…”
Section: Migraine Aura and Patent Foramen Ovalementioning
confidence: 99%
“…Інші теорії МІ пов'язані з ендотеліальною дисфункцією та гіперкоагуляцією під час аури [15]. Також, мігрень може бути асоційована з певними патологічними станами (наприклад, відкрите овальне вікно [16] і диссекція хребтової артерії [17]). Той факт, що певні генетичні синдроми (наприклад, церебральна аутосомно-домінантна артеріопатія з підкірковими інфарктами та лейкоенцефалопатією -CADASIL) асоціюються з мігренню та інсультами, може свідчити про генетичні механізми, і, ймовірно, вроджені зміни стінки дрібних мозкових судин [18].…”
Section: результати та їх обговоренняunclassified